Responsibility Of Doctors Who Perform Malpractices (An Overview Under Health Law) - Benny L H Hutahaean (Journal of Law Science, 2020)
The public's trust and positive assessments of the medical world are starting to decline, the medical world that used to seem unreachable by the law can now become a legal problem. This can be seen from the news that is reported by various mass media, both print and electronic media, there are often legal cases both civil and criminal which are examined by the Court related to medical practice or are often mentioned by many groups as: “Malpractice Medical". The problems that will be discussed by the author in writing this thesis are: What are the limitations that can be used to determine that a doctor has committed medical malpractice on a patient; What actions or legal remedies can a patient or his family take if he is exposed to medical malpractice; What sanctions can be imposed on doctors who commit medical malpractice as a form of responsibility of doctors to their patients. The type of research used in this paper is a normative juridical research, namely research conducted on written regulations governing health law and legal materials related to medical malpractice.